Protocol Analysis: 2.4 GHz Interference Frequency in the IEEE802.3ab Protocol - Juwari, Juwari; Asyhari, Moch Yusuf; Susanti, Pratiwi; Cahyono Putro, Moh Rizal Bagus (International Journal of Multidisciplinary Sciences and Arts, 2024)
Interference at the 2.4 GHz frequency is currently a significant problem in wireless networks. Especially on networks with environmental conditions where there are many active devices at the same time. This study analyzes the impact of interference on Delay and Jitter on IEEE 802.3ab protocol networks. The IEEE 802.3ab protocol is commonly known as the Gigabit Ethernet Protocol which already supports data transmission speeds of up to 1 Gbps. This study conducts various scenarios and simulates when interference occurs using five active access points (APs). The device's access points (APs) are all using the same 2.4 GHz frequency and channel. The data collection method uses the Wireshark application to measure the Delay and Jitter values at different interference levels. The results of simulations and tests with various scenarios show that there is a relationship between increased interference and Delay values. The Delay value is 14.129 ms when using a single AP without Interference. The Delay value increases to 1076,3730 ms in the event of interference with five APs. The jitter value increased from 0,2109 ms without interference. However, if there is interference with the active AP as much as 5 Jitter values to 17,9396 ms. Research shows that the jitter value is according to the TIPHON standard in the "Good" range. Meanwhile, the Delay value decreased significantly until it reached the "Poor" category when five APs were active. This research focuses on the need and importance of effective interference management to maintain network quality in interference-dense environments. This shows that optimizing for channel selection and frequency management is essential to reduce latency and improve transmission stability.